Genomic characterization and phylogenetic analysis of chloroplast genome of Eurya nitida (Eurya Thunberg) - Yuyu Han; Dongzhen Jiang; Lei Zhou; Tao Jiang (Mitochondrial DNA. Part B. Resources)
This study aimed to characterize the chloroplast genome of Eurya nitida Korthals. The complete chloroplast genome of Eurya nitida was sequenced and assembled using high-throughput sequencing technology. The genome spans 157,191 bp and exhibits a typical quadripartite structure, comprising a large single-copy region (LSC, 87,231 bp), a small single-copy region (SSC, 18,215 bp), and two inverted repeat regions (IRs, 51,744 bp each). Phylogenetic analysis revealed a close relationship between E. nitida and Eurya hebeclados Ling. This study elucidates the structural features and phylogenetic position of the E. nitida chloroplast genome.